COMPARISON OF EFFICACY AND SAFETY SILODOSIN 8 MG ONCE DAILY AND SILODOSIN 4 MG TWICE DAILY IN BPH PATIENTS WITH LUTS - Diansyah, Ramzie Nendra; Renaldo, Johan; Djatisoesanto, Wahjoe; Hakim, Lukman (Indonesian Urological Association, 2019)
Objective: This study was aimed to compare the efficacy and side effect of silodosin 8mg once daily and silodosin 4mg twice daily in BPH-LUTS patients after 4 and 12 weeks. Material & Methods: Single blind randomized controlled trials in 60 male patients aged ≥45 years with BPH-LUTS from July 2017 to October 2017 was divided into groups who received 8mg of silodosin once daily and those who received 4mg of silodosin twice daily. Efficacy and adverse events were evaluated after 4 and 12 weeks of treatment. Results: There was no significant difference of mean age of the two groups was 67.93 ± 6.49 years and 69.07 ± 6.28 years respectively (p 0.49). Both doses of this drug decreased the International Prostate Symptom Score (IPSS) and significantly increased the maximum urinary flow (Qmax) (p<0.05) but there was no significant differences between the two groups (p>0.05). Ejaculation disorder was the most common side effect in all groups (6.7% and 5%) and there was no significant difference between the two groups (p>0.05). Conclusion: The administration of 8mg of once daily silodosin has similar efficacy as 4mg twice daily silodosin. There were no adverse events differences in the two groups. Ejaculation disorder is the most common adverse event of silodosin administration.